Odpowiedź :
Odpowiedź:
a) JEST TOŻSAMOŚCIĄ
b) JEST TOŻSAMOŚCIĄ
c) JEST TOŻSAMOŚCIĄ
Szczegółowe wyjaśnienie:
[tex]sin^{2} x+cos^{2} x=1[/tex] , [tex]tgx = \frac{sinx}{cosx}[/tex] , [tex]ctgx = \frac{cosx}{sinx}[/tex]
a) sinx[tex]cos^{2} x[/tex] + [tex]sin^{3} x[/tex] = sinx
L = sinx[tex]cos^{2} x[/tex] + [tex]sin^{3} x[/tex] = sinx * ( [tex]cos^{2} x+sin^{2} x[/tex] ) = sinx * 1 = sinx = P
b) tgx * ctgx - [tex]sin^{2} x[/tex] = [tex]cos^{2} x[/tex]
L = [tex]tgx * ctgx -[/tex] [tex]sin^{2} x[/tex] = [tex]\frac{sinx}{cosx}[/tex] * [tex]\frac{cosx}{sinx}[/tex] - [tex]sin^{2} x[/tex] = 1 - [tex]sin^{2} x[/tex] =
= [tex]sin^{2} x+cos^{2} x - sin^{2} x[/tex] = [tex]cos^{2} x[/tex] = P
c) 2[tex]cos^{2} x[/tex] tgx + 1 = ( sinx + cosx [tex])^{2}[/tex]
L = 2[tex]cos^{2} x[/tex] * [tex]\frac{sinx}{cosx}[/tex] + 1 = 2 * cosx * sinx + 1 = 2sinxcosx + [tex]sin^{2} x+cos^{2} x[/tex] =
= [tex]sin^{2} x+ 2sinxcosx+cos^{2} x[/tex] = ( sinx + cosx [tex])^{2}[/tex] = P